TRANSFORMASI USAHA SAMPAN PADA KELOMPOK MASYARAKAT SUNGAI MELALUI OTOMATISASI DAN STRATEGI PEMASARAN INOVATIF - Sukardi, Sukardi; Fadhilah, Raudhatul; Gunarto, Gunarto; Irawan, Doddy; Alfian, Rudi (Jurnal Abdi Insani, 2024)
Area-based development emphasizes the optimal management of local resources to achieve community welfare. Kampung Beting, Pontianak, has great potential in transportation and river tourism but is hindered by a negative stigma as a center for drug trafficking. Through community service programs, business transformation is applied to the boat mining group with automation, installing waterproof canopies, using solar cell lights, and rebranding. The results show increased operational efficiency, revenue, and a regional image change. Innovative marketing strategies that capitalize on historical and cultural potential have successfully enhanced tourist attraction and local community welfare.